Design and Simulation of CNC Milling Machine on Matlab - Gumono Gumono; Mira Mira; Samsul Hadi; Rilis Eka Perkasa (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2021)
The development and revision of milling machines and components are continuous. With the help of computer technology, we can simulate some activities in a manufacturing system. The main purpose of a simulation is to understand and imitate the behavior of a particular manufacturing system on a computer, before hardware creation, thereby reducing the amount of testing and experimentation in the field. By using a virtual system, less material is wasted and the constraints on the actual operation of the machine in the field can be minimized. In the field of milling machinery, various modeling and simulation methods have been introduced so far. Today, the manufacture of a machine tool can no longer use the time-consuming and costly manufacturing and testing of physical prototypes to detect weak points and then optimize the design. In contrast, the current machine tool design process uses